Achieving data security and privacy across healthcare applications using cyber security mechanisms. Issue 5 (3rd December 2020) - Zhu, Shanying; Saravanan, Vijayalakshmi; Muthu, BalaAnand
Abstract : Purpose: Currently, in the health-care sector, information security and privacy are increasingly important issues. The improvement in information security is highlighted in adopting digital patient records based on regulation, providers' consolidation, and the growing need to exchange information among patients, providers, and payers. Design/methodology/approach: Big data on health care are likely to improve patient outcomes, predict epidemic outbreaks, gain valuable insights, prevent diseases, reduce health-care costs and improve analysis of the quality of life. Findings: In this paper, the big data analytics-based cybersecurity framework has been proposed for security and privacy across health-care applications. It is vital to identify the limitations of existing solutions for future research to ensure a trustworthy big data environment. Furthermore, electronic health records (EHR) could potentially be shared by various users to increase the quality of health-care services. This leads to significant issues of privacy that need to be addressed to implement the EHR. Originality/value: This framework combines several technical mechanisms and environmental controls and is shown to be enough to adequately pay attention to common threats to network security.